El silencio administrativo y sus efectos jurídicos en la legislación ecuatoriana - Lopez Carriel, Dorys Lucy (2014)
Article 66 paragraph 23 of the Constitution recognizes "the right to lodge complaints and petitions to the authorities, but in no case on behalf of the people, and to receive attention or relevant answers at the right time." However within the State Modernization Act legal effect to protect against downtime administered management parameters are not set. Given the above described problem I decided to develop this research work entitled "SILENCE ADMINISTRATIVE AND LEGAL EFFECTS IN LEGISLATION ECUATORIANA" in which I make a doctrinal and legal analysis of the issues raised, achieving demonstrate the failure of the law and the need urgent legislation to create an enabling better implementation of administrative silence. Therefore in this work the theoretical arguments, results of field research, in which analyzes the necessity of creating a legal system that provides a better implementation of administrative silence shows are collected, this being the main idea of my thesis work , which I hope will help to solve this problem.